Identification of RNA-binding domains of RNA-binding proteins in cultured cells on a system-wide scale with RBDmap - Castello, Alfredo; Föhr, Sophia; Krijgsveld, Jeroen; Hentze, Matthias W. (Nature protocols, 2017)
This protocol is an extension to: Nat. Protoc. 8, 491-500 (2013); doi:10.1038/nprot.2013.020; published online 14 February 2013RBDmap is a method for identifying, in a proteome-wide manner, the regions of RNA-binding proteins (RBPs) engaged in native interactions with RNA. In brief, cells are irradiated with UV light to induce protein-RNA cross-links. Following stringent denaturing washes, the resulting covalently linked protein-RNA complexes are purified with oligo(dT) magnetic beads. After elution, RBPs are subjected to partial proteolysis, in which the protein regions still bound to the RNA and those released to the supernatant are separated by a second oligo(dT) selection. After sample preparation and mass-spectrometric analysis, peptide intensity ratios between the RNA-bound and released fractions are used to determine the RNA-binding regions. As a Protocol Extension, this article describes an adaptation of an existing Protocol and offers additional applications. The earlier protocol (for the RNA interactome capture method) describes how to identify the active RBPs in cultured cells, whereas this Protocol Extension also enables the identification of the RNA-binding domains of RBPs. The experimental workflow takes 1 week plus 2 additional weeks for proteomics and data analysis. Notably, RBDmap presents numerous advantages over classic methods for determining RNA-binding domains: it produces proteome-wide, high-resolution maps of the protein regions contacting the RNA in a physiological context and can be adapted to different biological systems and conditions. Because RBDmap relies on the isolation of polyadenylated RNA via oligo(dT), it will not provide RNA-binding information on proteins interacting exclusively with nonpolyadenylated transcripts. Applied to HeLa cells, RBDmap uncovered 1,174 RNA-binding sites in 529 proteins, many of which were previously unknown.
Gesehen am 15.10.2018